Oscillating magnetic field effects on the yields of radical pair reactions - Timmel, C; Hore, P (1996)
The effects of fluctuating magnetic fields on the yields of chemical reactions are explored within the radical pair mechanism, for the case in which singlet and triplet radical pairs disappear at equal rates. Approximate analytical expressions and exact numerical calculations are used to discuss the origin of the oscillating magnetic field effect (OMFE), its likely magnitude, and its dependence on radical pair lifetime, magnetic field strength and frequency. Changes in product yields of up to 25% are predicted for fields at frequencies corresponding to hyperfine splittings (1-100 MHz) in the radicals. The largest effects are expected when the singlet-triplet interconversion induced by the oscillating field is much faster than the rate of reaction of the radical pair. The likelihood of observing the OMFE experimentally is discussed.